The Efficacy of Cognitive Behavioural Therapy on Substance Use and Eating Disorders Among In-School Adolescents in Taraba State, Nigeria - Emmanuel, Atsue Terhile (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This study investigated the efficacy of Cognitive Behavioural Therapy (CBT) on specific mental health disorders among in-school adolescents in Taraba State, Nigeria. A quasi-experimental research design was employed, guided by two research questions and two null hypotheses tested at a 0.05 level of significance. The population comprised 200,382 in-school adolescents across 380 public secondary schools in the state. A sample of 248 adolescents from two schools was selected for the study. Data were collected using a self-structured instrument, the “Mental Health Disorder Questionnaire (MHDQ).” Analysis involved mean and standard deviation for the research questions and Analysis of Covariance (ANCOVA) for the hypotheses. The findings revealed significant post-test differences between the experimental and control groups. The experimental group exhibited a significant reduction in symptoms of substance use disorders and a lower prevalence of eating disorders compared to the control group. The study concluded that CBT is an effective intervention for reducing these mental health disorders. Recommendations include implementing school-based CBT programs by substance abuse counsellors to address triggers and coping mechanisms, and for health coordinators to promote CBT sessions that challenge cognitive distortions related to body image to foster positive eating habits.